The Relationship between Immigration and Trade in Canada: an Econometric Model - Ma, Chao (Université d'Ottawa | University of Ottawa, 2014)
A positive relationship between immigration and trade has been found in previous studies, though the magnitude of such relationship varies among different countries under estimation. This paper intends to find the trade creation impact of immigration stock in Canada during the period of 1990 to 2012 employing an augmented gravity model. I find that there is a robust and positive relationship between immigrant stock and Canadian bilateral trade with the source countries of immigration. A 10% increase in immigration stock leads to a 1.71% increase in exports and a 2.20% increase in imports. I also find that immigrant stock has a larger import-creation impact than an export-creation impact through the preference channel of immigration. Finally, I find that the immigration impact from lower-income countries on Canadian trade is stronger than that from higher-income countries